Implementasi Metode Problem Based Learning Dalam Pembelajaran Pendidikan Agama Islam Di SMP Negeri 02 Kajen Kabupaten Pekalongan - Khasan Mursyidi; Muhammad Hufron (https://ejournal.insuriponorogo.ac.id/, 2023)
There are still many conventional learning practices. Teachers dominate learning while students are only recipients of knowledge. Good learning is learning that increases the potential of students. There are many things that can be done to achieve this. One effort that can be made is by choosing the right learning method. A method that is not boring, not monotonous, and can build students' enthusiasm for learning. The formulation of the problem in this research is how to implement the problem based learning method in learning Islamic religious education at SMP Negeri 02 Kajen Kajen, Pekalongan Regency and what are the supporting factors and inhibiting factors for implementing the problem based learning method in learning Islamic religious education at SMP Negeri 02 Kajen Kajen Regency Pekalongan. This research uses a qualitative approach and is field research. The data collection techniques used were interviews and documentation. The data analysis technique used is triangulation analysis with steps to match data from various data sources. The results of this research indicate that the implementation of the problem based learning method in Islamic religious education learning at SMP Negeri 02 Kajen is in accordance with the PBL learning syntax, namely through 5 stages, Stage (1) orienting students towards the problem and stage (2) organizing students to realize in preliminary learning activities in the form of giving problems and dividing into groups. Stage (3)guiding the investigation, stage (4) developing and presenting the work stage and stage (5) analyzing and evaluating the results of problem solving manifested in core activities in the form of group discussions and presentations. Meanwhile, supporting factors for method implementation include teacher readiness, student activity, environment and infrastructure. . The inhibiting factors include lack of student participation, lack of teacher mastery in presenting students' methods and abilities.